Intrinsic lamellar defects containing atomic Cu in Cu2X (X = S, Se) thermoelectric materials. Issue 12 (15th March 2021) - Wei, Yuyu; Lu, Ping; Zhu, Chenxi; Zhao, Kunpeng; Lu, Xiaoyue; Su, Hong; Shi, Xun; Chen, Lidong; Xu, Fangfang
Abstract : Intrinsic lamellar defects containing atomic copper have been revealed in Cu2 X (X = S, Se) materials by structural and chemical analysis at the atomic scale, providing new insight into the investigation of the copper precipitation mechanism. Abstract : As liquid-like materials, Cu2 X (X = S, Se) binary compounds and their solid solutions possess excellent thermoelectric performance but poor stability. Precipitation of copper metal onto the bulk surface under electric or temperature fields is one of the trickiest problems limiting the application of Cu2 X (X = S, Se) in thermoelectric devices. Here, high density lamellar defects consisting of close-packed S/Se double layers have been observed in Cu2 S, Cu2 Se and Cu2 S0.5 Se0.5 . Electron energy-loss spectroscopic analyses in the atomic scale surprisingly found that the copper element shows the characteristic of an atom in the close vicinity of the lamellar defects. Such a configuration should have originated from the small electronegativity discrepancy between copper and sulfur/selenium. The as-observed lamellar defects and atomic copper provide new insight into the investigation of copper precipitation problems. Meanwhile, their formation in high density also suggests their important roles in thermoelectric properties.